2010
DOI: 10.1111/j.1365-2443.2010.01426.x
|View full text |Cite
|
Sign up to set email alerts
|

p62/SQSTM1 cooperates with Parkin for perinuclear clustering of depolarized mitochondria

Abstract: PINK1 and Parkin were first identified as the causal genes responsible for familial forms of early-onset Parkinson's disease (PD), a prevalent neurodegenerative disorder. PINK1 encodes a mitochondrial serine ⁄ threonine protein kinase, whereas Parkin encodes an ubiquitin-protein ligase. PINK1 and Parkin cooperate to maintain mitochondrial integrity; however, the detailed molecular mechanism of how Parkin-catalyzed ubiquitylation results in mitochondrial integrity remains an enigma. In this study, we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
344
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(391 citation statements)
references
References 52 publications
42
344
3
2
Order By: Relevance
“…This is recognized as a signal to recruit the E3 ligase parkin from the cytosol to the mitochondria (Narendra et al 2010b). Here, parkin tags several mitochondrial outer membrane proteins with K63-and K27-linked poly-ubiquitin chains (Narendra et al 2010a;Geisler et al 2010a;Okatsu et al 2010). Once the mitochondrial proteins are tagged with ubiquitin, p62/SQSTM1 associates with them and drives the whole organelle into sequestosomes that are then cleared by autophagy (Narendra et al 2010a;Geisler et al 2010a).…”
Section: Autophagy and Protein Degradationmentioning
confidence: 99%
“…This is recognized as a signal to recruit the E3 ligase parkin from the cytosol to the mitochondria (Narendra et al 2010b). Here, parkin tags several mitochondrial outer membrane proteins with K63-and K27-linked poly-ubiquitin chains (Narendra et al 2010a;Geisler et al 2010a;Okatsu et al 2010). Once the mitochondrial proteins are tagged with ubiquitin, p62/SQSTM1 associates with them and drives the whole organelle into sequestosomes that are then cleared by autophagy (Narendra et al 2010a;Geisler et al 2010a).…”
Section: Autophagy and Protein Degradationmentioning
confidence: 99%
“…Several groups have reported that p62 is involved in mitophagy (the autophagic degradation of mitochondria); however, it is not clear whether p62 is required for targeting of ubiquitylated mitochondria to autophagosomes or serves a different functional role (Ding et al, 2010;Geisler et al, 2010;Narendra et al, 2010;Okatsu et al, 2010). Recently, we showed that p62 is involved in selective degradation of peroxisomes when peroxisomes were labeled with ubiquitin .…”
Section: Introductionmentioning
confidence: 99%
“…1,36 In neuronal cells, SQSTM1 is required for ubiquitination-dependent clustering of damaged mitochondria caused by treatment with a mitochondrial uncoupler, carbonyl cyanide m-chlorophenylhydrazone. 6,18,37 Thus, we hypothesized that SESN2 may induce perinuclear clustering of mitochondria by mediating the aggregation of SQSTM1 via SESN2-SQSTM1 interaction and by linking SQSTM1 to ubiquitins on the surface of damaged mitochondria. As shown in Fig.…”
Section: Sesn2 Induces Mitochondrial Priming By Facilitating Perinuclmentioning
confidence: 99%
“…7,14,15 Activated PARK2 promotes ubiquitination of outer membrane proteins on the mitochondria, which in turn triggers translocation of the ubiquitin-binding receptor SQSTM1 or NBR1 (neighbor of Brca1 gene 1) to mitochondria, thus completing mitochondrial priming. 6,[16][17][18][19] Among the components of the autophagy machinery required for mitophagy, ULK1 and BNIP3L (BCL2/adenovirus E1B 19kDa interacting protein 3-like), are critical for clearance of mitochondria during erythroid cell maturation. 2,20,21 However, it remains unclear how these 2 steps are connected so that the mitophagy process can be completed under inflammatory conditions.…”
Section: Introductionmentioning
confidence: 99%